SYMMETRY ANALYSIS ON - Jessada Tanthanuch (Proceedings of ICMSA, 2006)
Equationis a delay partial differential equation with an arbitrary functional G. Group analysis method is applied to find symmetries of the equation and to make group classification. Representations of analytical solutions and reduced equations are obtained from the symmetries.